Effect of lecithin incorporation on the physical properties of dark chocolates - Oblitas, Robin (2023)
The study of viscosity and texture in chocolates facilitates the generation of new important information for the production and development of this product, and thus avoid defects during processing, including the variety of cocoa beans used to make the chocolates. For this reason, the objective was to evaluate the rheological and textural behavior of dark chocolates made with Criollo and CCN-51 cocoa beans with the addition of lecithin. Dark chocolate bars were made with 70% of the two cocoa varieties and lecithin was added (0.2-0.4g/100g). The samples were tested for viscosity in a rheometer and texture (hardness) in a texturometer. As a result, the chocolates made with beans of the two varieties presented different viscosity and hardness, due to the fact that the composition of the cocoa beans is different and the addition of lecithin influenced these properties, decreasing their viscosity and texture (hardness).